Differential analysis of transient increases of serum cTnI in response to handling in rats. Issue 2 (5th December 2013) - Mikaelian, Igor; Dunn, Michael E.; Mould, Diane R.; Hirkaler, Gerard; Geng, Wanping; Coluccio, Denise; Nicklaus, Rosemary; Singer, Thomas; Reddy, Micaela
Abstract Serum cardiac troponins are the key biomarkers of myocardial necrosis in humans and in preclinical species. The use of ultrasensitive assays for serum cardiac troponin I (cTnI) as a biomarker in safety studies is hampered by interindividual differences. In this study, we investigated the effect of handling procedures on serum cTnI and explored modeling and simulation approaches to mitigate the impact of these interindividual differences. Femoral‐catheterized male Crl:WI(Han) rats (n = 16/group) were left undisturbed in their cages with no handling; subjected to 5 min of isoflurane/O2 anesthesia (A); or placed into a rodent restrainer followed by simulated tail vein injection (RR). Serum cTnI concentrations were assessed over a 24‐h period using an ultrasensitive assay, and the study was repeated for confirmation. The mean serum cTnI concentration pre‐procedure was 4.2 pg/mL, and remained stable throughout the duration of the study in the rats submitted to the A procedure. Serum cTnI concentrations increased transiently after the RR procedure with a median time to maximum concentration (Tmax), of 1 and 2 h and a mean maximum value concentration (Cmax), of 53.0 and 7.2 pg/mL in the initial and repeat studies, respectively. A population pharmacodynamic model identified interindividual, procedure‐ and study‐specific effects on serum cTnI concentrations in rats. It is concluded that a modeling and simulation approach more appropriately describes and statistically analyzes the data obtained with this ultrasensitive assays.